Campanha de conscientização de violência de gênero para servidoras da Universidade Federal do Amazonas - Mendes, Lívia Priscila de Souza (Brasil, 2022)
This work presents the results of a research on moral and sexual harassment suffered by UFAM servants. Based on the observation and the need to talk about the subject, a campaign was carried out with the aim of encouraging women and raising awareness that harassment is a crime and that it should be talked about. In this sense, a Public Relations campaign was developed for the institution, whose products are video, banner, posters, folders and billboard. Initially, the proposal is to develop a pilot of the campaign in the building of the Rectory of UFAM so, after its evaluation, its reach can be covered to the servers and students of Campus Capital and Interior, and that the entire university community knows what is happening. in the institutional scope or in the University environments and that we can leave this matter clarified, because this is not normal!